Mixed signals: employee reactions to talent status communication amidst strategic ambiguity. Issue 4 (21st February 2020) - Sumelius, Jennie; Smale, Adam; Yamao, Sachiko
Abstract: Given the sensitive nature of communicating talent status in an 'exclusive' talent management system and the complexity involved in simultaneously sending signals of exclusivity and inclusivity, some organisations avoid open communication and instead opt for 'strategic ambiguity' – intentionally maintaining an element of secrecy and information asymmetry. However, we know relatively little about the effects of this communication approach as a feature of the organisational context on the reactions of employees. Drawing on signalling theory, we examine the reactions of both talents and 'B' players on finding out about their talent status in the context of a company that adopts strategic ambiguity in its communication about talent. The data consists of 24 in-depth, qualitative interviews with individuals with experience of TM in a Finnish subsidiary of a large, US-based multinational corporation. The findings reveal that the contextual effects of strategic ambiguity in talent communication affected the reactions of talents and 'B' players in distinctly different ways, but had few long-term positive effects on the attitudes and behaviours of either group. These findings present important theoretical and practical implications for the role of communication and organisational context in employee reactions to talent pool inclusion and for talent management more generally.